Relationship between balance and running tests in adolescent football players - Sikora, D.; Ploszczyca, K.; Sójka, A.; Linek, P. (Trends in Sport Sciences, 2025)
Introduction: Football is a sport that requires a variety of motor skills during both high- and low-intensity efforts. Motor abilities such as speed, endurance and balance are crucial in adolescent football players; it is likely that performance on individual tests assessing each motor ability should show some relationships.